PBL Methodology: Enhancing Science and Mother Tongue Integration - Vaz, Odete (2020)
Curricular integration in school usually departs from a theme that reveals potential to interrelate knowledge from different disciplinary areas. However, an integrated approach can also be achieved by following a certain didactic line, problem situation or activity. In this study, a Problem Based Learning (PBL) methodology was implemented with the intention of promoting better learning in the fields of Science and Mother Tongue (Portuguese). This methodology has been used at different levels of schooling, especially related with Science learning, and our aim was to verify its potential to the improvement of expository text production. The participants were 44 pupils from the 4th grade of a primary state school, aged between 8-9 years old, divided into two groups (the experimental one and the control one). To achieve the established aim, three activities related to topics of the science syllabus were designed in accordance with PBL principles, that are: a) to present a problem that is relevant in a real context; b) to frame it using a real or a fictional scenario that can motivate pupils c) to give data sources to help its resolution; d) to promote collaborative work; e) to help pupils dealing with the proposed data sources through a tutorial process; f) to ask for a final product in which the answer to the problem is included; g) to assess all the learning process, presenting new situations that imply the knowledge acquired. The study took place during three months and the written productions of pupils were assessed with the help of grids for learning verification of scientific concepts and internalization of the key dimensions associated with written text production. The control group had a traditional approach of the contents of both disciplines. The results were particularly encouraging in the experimental group in terms of the presented aims, and reveled that the use of PBL can help learning in the two subject areas involved. It was also verified that the use of PBL activities had an impact on communication skills of pupils as well as in their motivation for learning.